If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -15 + 5(-2) = -5y Multiply 5 * -2 -15 + -10 = -5y Combine like terms: -15 + -10 = -25 -25 = -5y Solving -25 = -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. -25 + 5y = -5y + 5y Combine like terms: -5y + 5y = 0 -25 + 5y = 0 Add '25' to each side of the equation. -25 + 25 + 5y = 0 + 25 Combine like terms: -25 + 25 = 0 0 + 5y = 0 + 25 5y = 0 + 25 Combine like terms: 0 + 25 = 25 5y = 25 Divide each side by '5'. y = 5 Simplifying y = 5
| 3x(3x+2)=3x-4 | | -15+5(0)=-5y | | 9x+25=43 | | -15+5(2)=-5y | | -2(2x-6)=32 | | 6x^2=x-24 | | 7x-10+x+4=90 | | -4=(-2) | | -4=(0) | | 7x-10+x+4=180 | | 24x-3y-18=0 | | -2=(2) | | 2pq+pq= | | 6*(x+2)= | | (-14)+3= | | 2+3y=19 | | -4=2 | | 4+x=-10 | | 4x+21+11x+9=180 | | 9g-13=2g | | 7-15=-(3-8) | | 3n+7=4 | | 7x-10=x+4 | | y+2=-3(-2)+8 | | c+6=-3 | | y+2=-3(0)+8 | | -3.1+x=-2.1 | | 6a-3=2 | | y+2=-3(2)+8 | | -3x(2x-3)=-5x+5 | | 6n+3=-2n+12 | | 6+3=3-3y |